PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATA PELAJARAN IPS PESERTA DIDIK KELAS VIII - Pratama, Hendri; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This proposal is named "The Impact of The capacity to understand individuals on a profound level on Learning Results of Social Examinations Subjects for Class VIII An Understudies of SMPN 4 Sungai Raya, Kubu Raya Regime". This exploration was led by unmistakable examination technique utilizing a quantitative methodology. The exploration strategy utilized is circuitous correspondence procedure and narrative review method with information assortment devices as surveys and documentation. In view of the consequences of the examination and conversation, the accompanying ends can be drawn: 1) The capacity to understand people on a deeper level on friendly investigations learning results for class VIII An understudies of SMPN 4 Sungai Raya, Kubu Raya Rule is for the most part remembered for the classification of concur or great with a level of 68%. 2) Learning results in friendly examinations subjects for class VIII An understudies of SMPN 4 Sungai Raya, Kubu Raya Rule should be visible from the adjustment of the typical worth of the first semester MID trial of understudies which was initially in class VIII A simply 64.44 changed to 86.69 on the test. MID semester 2. 3) The Impact of The capacity to understand people on a profound level on Learning Results of Social Examinations Subjects for Class VIII An understudies of SMPN 4 Sungai Raya, Kubu Raya Regime. The Impact of The capacity to understand individuals on a deeper level on Learning Results of Social Investigations Subjects Class VIII A SMPN 4 Sungai Raya Kubu Raya Regime is 7.4% with a coefficient of assurance of 0.271.